2006
DOI: 10.1158/1078-0432.ccr-06-0511
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Study of Intravenous LBH589, a Novel Cinnamic Hydroxamic Acid Analogue Histone Deacetylase Inhibitor, in Patients with Refractory Hematologic Malignancies

Abstract: Purpose: LBH589 is a novel histone deacetylase inhibitor that inhibits proliferation and induces apoptosis in tumor cell lines. In this phase I study, LBH589 was administered i.v. as a 30-minute infusion on days 1to 7 of a 21-day cycle. Experimental Design: Fifteen patients (median age, 63 years; range, 42-87 years) with acute myeloid leukemia (13 patients), acute lymphocytic leukemia (1 patient), or myelodysplastic syndrome (1 patient) were treated with LBH589 at the following dose levels (mg/m 2 ): 4.8 (3 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
197
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 298 publications
(205 citation statements)
references
References 11 publications
6
197
0
2
Order By: Relevance
“…Here we demonstrate that LBH589 alone, in nanomolar range which is far from toxic range in humans [28], is able to reduce the viability of ER-positive MCF-7…”
Section: Discussionmentioning
confidence: 71%
“…Here we demonstrate that LBH589 alone, in nanomolar range which is far from toxic range in humans [28], is able to reduce the viability of ER-positive MCF-7…”
Section: Discussionmentioning
confidence: 71%
“…[25][26][27][28] Phase I clinical trials have also shown that some HDACi, such as suberoylanilide hydroxamic acid (SAHA), panobinostat and belinostat, are able to reduce tumor burden in patients with MM. [29][30][31] However, it is unclear, besides the direct in vitro effects on MM cells, how the BM microenvironment is affected by these HDACi, and more specifically how crucial processes like induction of bone disease and angiogenesis are affected.…”
Section: Introductionmentioning
confidence: 99%
“…It showed poor oral bioavailability in rodents (F=6% in rats) and moderate F in dogs (33-50%) (Konsoula et al, 2009). Like SAHA, Panabinostat was first tried as an intravenous formulation in the phase 1 clinical trials (Giles et al, 2006). In that study, LBH589 showed dose proportional increase in C max and AUC between 4.8 and 14 mg/m 2 , with the terminal half-life ranging between 8-16 h. The V ss and CL were not reported.…”
Section: Panabinostat (Lbh589)mentioning
confidence: 99%